The Role of Strategic Planning in Improving Engineering Project Performance According to Saudi Vision 2030. Case Study - Projects by Dar Al-Handasah - Othman, Nazar Mohamed Elkheir Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The study addressed the role of strategic planning in improving the performance of engineering projects in light of the Kingdom of Saudi Arabia’s vision. The problem of the study lies in the fact that the performance of engineering projects in both public and private sector companies in Saudi Arabia needs further development to keep pace with technological advancements and economic and technological changes in the regional and international environment, especially in light of the Kingdom’s direction towards artificial intelligence technologies and effective strategic planning. The study aimed to identify the role of strategic planning in enhancing the performance of engineering projects in Saudi Arabia and the possibility of benefiting from artificial intelligence tools and techniques to improve the efficiency of project performance in engineering companies in both sectors. In this research, we present a case study of Dar Engineering Consulting Company, where the importance of the study arises from the vitality of the subject itself as it focuses on linking effective strategic planning with the efficiency of engineering project performance. The study relied on descriptive and historical methodologies and reached several important findings, including: the vision and mission of engineering companies align with the goals of the Kingdom of Saudi Arabia’s vision. Some engineering companies do not pay attention to analyzing the internal and external environment, opportunities, and threats, which has affected the development of project performance. Some companies lack the use of artificial intelligence techniques in strategic analysis, which has contributed to the poor quality of strategic plans. Based on these findings, the study presented a set of recommendations, the most important of which are: the necessity of benefiting from artificial intelligence technologies in developing performance improvement plans and strategies for engineering projects. The necessity of benefiting from successful global experiences in effective strategic planning to enhance the performance of engineering projects.